2020
DOI: 10.1111/jcpt.13195
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Incorporating Clinical Pharmacists in an Adult Intensive Care Unit: A Cost‐saving Study

Abstract: What is known and objective A framework to evaluate the impact of clinical pharmacists in intensive care units (ICUs) in Chile has not yet been established. This study evaluates the cost avoidance and cost‐benefit ratios of clinical pharmacist interventions in terms of treatment optimization in an adult ICU in southern Chile. Methods Clinical pharmacist interventions in a multidisciplinary adult ICU were assessed between January and December 2019. Only interventions suggested by pharmacists and accepted by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
(27 reference statements)
0
5
0
1
Order By: Relevance
“…In 2017, a decree was published in the Official Journal of the Republic of Chile where the subspecialty of Clinical Pharmacy was acknowledged as a certified specialty executed by health providers in the country. 29 32,33 Some of the most notable innovations in clinical pharmacy in Chile include the development of advanced clinical pharmacokinetics, 34 recognition of pharmaceutical specialties, elaboration of clinical guides, and collaboration with clinical teams specialized in the assistance of complex patients. 35 In addition, networking for the development of Clinical Pharmacogenetics in complicated pathologies has become important.…”
Section: Universidade De São Paulo and Universidade Federal De Ouromentioning
confidence: 99%
See 2 more Smart Citations
“…In 2017, a decree was published in the Official Journal of the Republic of Chile where the subspecialty of Clinical Pharmacy was acknowledged as a certified specialty executed by health providers in the country. 29 32,33 Some of the most notable innovations in clinical pharmacy in Chile include the development of advanced clinical pharmacokinetics, 34 recognition of pharmaceutical specialties, elaboration of clinical guides, and collaboration with clinical teams specialized in the assistance of complex patients. 35 In addition, networking for the development of Clinical Pharmacogenetics in complicated pathologies has become important.…”
Section: Universidade De São Paulo and Universidade Federal De Ouromentioning
confidence: 99%
“…Also, the involvement of clinical pharmacists in critical care teams, with their specialized knowledge of medications and their possible interactions and adverse effects, can provide valuable input and guidance to ensure patients receive the appropriate medications and dosages in critical care settings, which can also have a positive impact in reducing health care expenditures. 30,32 6 | COLOMBIA Colombia, a South American country, covers an area of 1 141 748 km 2 and is home to a population of 48.26 million, according to the 2018 census. 36 Colombia began regulating the professional practice of pharmacists in 1962.…”
Section: Universidade De São Paulo and Universidade Federal De Ouromentioning
confidence: 99%
See 1 more Smart Citation
“…In the current hospital services, especially the treatment with high cost, the intervention of pharmacists can have a beneficial impact on the economic effect. Studies related to nursing in intensive care unit have shown that the addition of pharmacists can optimize the treatment plan and reduce the unnecessary use of drugs, therefore, making it effective in reducing the cost of medication: Pharmacists can reduce the improper use of albumin in the intensive care unit, decrease the amount and cost of albumin, and save about $355000 a year in ICU [42]; And a study, evaluating the intervention of pharmacists in adult intensive care units, also showed that pharmacists participating in a multidisciplinary ICU team, could provide meaningful intervention advice to the medical team and reduce drug costs, saving the team about $263000 in one year [43]. Surgery or chronic diseases also cost a lot of medical expenses, and studies have shown that pharmacists can also use professional knowledge and skills to reduce the financial burden of patients: Allowing pharmacists to care for (TJA) patients undergoing total joint replacement optimizes drug treatment throughout the nursing process, which can save the institution a net cost of about $73000 per year [44]; A systematic review of the effects of pharmacists on nursing care for the prognosis of diabetes shows that such interventions can save about $80,000 per person per year compared with routine care.…”
Section: Economic Benefitmentioning
confidence: 99%
“…Asociado, diversos factores tales como la excesiva demanda y estrés asistencial, el desgaste de los equipos de salud y el temor al contagio por extubación accidental podría generar bruscas variaciones en la calidad de la atención y seguimiento de los pacientes, impactando principalmente en terapias que requieran titulación al lado de la cama del paciente o "bedside" como es el caso de analgésicos, sedantes, bloqueantes neuromusculares o vasoactivos, aumentando el riesgo errores de medicación y otros eventos adversos graves. En este sentido, la incorporación del farmacéutico como miembro del equipo multidisciplinario en UCI y sus intervenciones "bedside", así como el desarrollo de estrategias de optimización y protocolización farmacoterapéuticas, han demostrado ser medidas efectivas en disminuir los errores de medicación, el consumo de fármacos, sus costos asociados, los días de VMI, la estadía y mortalidad en UCI, ocupando los analgésicos y sedantes un lugar prioritario dentro de los grupos terapéuticos intervenidos 8,9 . El objetivo del presente trabajo es proveer un revisión no sistemática, basada en la evidencia disponible de sedación, analgesia y bloqueo neuromuscular en pacientes de UCI, como estrategia para el manejo óptimo de pacientes CO-VID-19 graves que requieren ingreso a unidades críticas, con un énfasis en el uso racional de las alternativas terapéuticas disponibles.…”
unclassified